2015
DOI: 10.3892/mmr.2015.3239
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced specific antitumor immunity of dendritic cells transduced with the glypican 3 gene and co-cultured with cytokine-induced killer cells against hepatocellular carcinoma cells

Abstract: Dendritic cell (DC)-based cancer immunotherapy requires an immunogenic tumor-associated antigen and an effective therapeutic strategy. Glypican 3 (GPC3) is a valuable diagnostic marker and a potential therapeutic target in hepatocellular carcinoma (HCC). The present study investigated whether DCs transduced with the GPC3 gene (DCs-GPC3) and co-cultured with autologous cytokine-induced killer cells (CIKs) may induce a marked specific immune response against GPC3-expressing HCC cells in vitro and in vivo. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Wang et al. constructed GPC3 ‐transduced DCs and cocultured them with autologous cytokine‐induced killer cells (CIKs) . These DC‐GPC3‐CIKs exerted a strong antitumor effect against GPC3‐expressing HCC cells both in vitro and in vivo.…”
Section: Gpc3‐targeted Therapies In Hccmentioning
confidence: 99%
“…Wang et al. constructed GPC3 ‐transduced DCs and cocultured them with autologous cytokine‐induced killer cells (CIKs) . These DC‐GPC3‐CIKs exerted a strong antitumor effect against GPC3‐expressing HCC cells both in vitro and in vivo.…”
Section: Gpc3‐targeted Therapies In Hccmentioning
confidence: 99%
“…Dendritic cells were transduced with the GPC3 gene (DCs GPC3) and cocultured with autologous cytokine‐induced killer cells (CIKs). It was reported that DCs GPC3 CIKs significantly enhanced the cytotoxic activity against GPC3‐expressing HepG2 cells and showed significant inhibition of tumor growth in nude mice . An immunotherapy using both α‐Gal epitope‐pulsed DCs and CIK cells was evaluated.…”
Section: Immunotherapeutic Strategiesmentioning
confidence: 99%
“…(4) DC‐CIK cells can kill many types of tumour cells and have the same potency against multidrug‐resistant tumour cells as they do against drug sensitive cells. (5) The tumour‐killing activity of DC‐CIK cells is not affected by immunosuppressive agents (such as cyclosporine and FK506), and DC‐CIK cells have very minimal toxicity against normal bone marrow haematopoietic precursor cells (less than 30%) …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] CIK cells have 2 major heterogeneous cell subpopulations, CD3+/CD56+ and CD3+/CD8+. [5][6][7][8][9] Some studies have indicated that CIK cells can readily recognise cancer cells and have the advantages of both the strong anti-tumour activity of T lymphocytes and the non-MHC-restricted tumour-killing ability of NK cells. [5][6][7][8][9] Dendritic cells (DCs) are professional antigen presenting cells (APCs) that have received attention in recent years.…”
Section: Introductionmentioning
confidence: 99%